Keberatan Pidana Perihal Kepemilikan Narkotika - Muhammad Djaelani (Universitas Islam Balitar, Blitar, 2023)
This research aims to provide a prescription regarding criminal objections regarding possession of narcotics. This research is normative research with a statutory approach and a case approach. Legal materials are laws, court decisions, and other official legal publications. The results of this research answer that legal advisors need efforts to build legal arguments based on 2 (two) things, namely existing facts and the application of the law. First, the existing facts attached to Rusdiadi must be tested again. Second, in the application of the law, there is a discrepancy in the application of Article 185 of the Criminal Procedure Code, the absence of Article 127 of the Narcotics Law, and a discrepancy in the application of Article 55 of the Criminal Code. Finally, reconstruction before taking legal action is very necessary for the defendant to examine the facts and the application of the law.